Biometric Parameters and Corneal Astigmatism: Differences Between Male and Female Eyes - De Bernardo M (Dove Medical Press, 2020)
Maddalena De Bernardo,1 Lucio Zeppa,2 Lucia Zeppa,2 Palmiro Cornetta,3 Livio Vitiello,1 Nicola Rosa1 1Department of Medicine, Surgery and Dentistry, “Scuola Medica Salernitana”, University of Salerno, Baronissi, Salerno, Italy; 2San Giuseppe Moscati Hospital, Avellino, Italy; 3Presidio Ospedaliero “Maria SS Addolorata”, ASL Salerno, Eboli, Salerno, ItalyCorrespondence: Maddalena De BernardoDepartment of Medicine, Surgery and Dentistry, “Scuola Medica Salernitana”, University of Salerno, Via Allende, Baronissi, Salerno 84081, ItalyTel/Fax +39 89 672407Email mdebernardo@unisa.itPurpose: To evaluate the gender-related differences in demographic and ocular biometric trends in a defined population presenting for consultation within the Italian public health system and to collect data of several ocular parameters at different stages of life, highlighting the differences between females and males.Patients and Methods: In this retrospective study, keratometry, corneal astigmatism, and axial eye length of 729 patients (729 eyes; mean age: 58± 21 years; range: 18– 96 years) were evaluated using partial coherence interferometry. Statistical evaluation was performed utilizing a paired t-test and R2 analysis.Results: In females (396 eyes of 396 patients), mean keratometry ranged between 40.59– 47.78 D (44.27± 1.36 D), corneal astigmatism ranged between 0– 3.82 D (1.13± 0.74 D), and axial length ranged between 20.5– 31.32 mm (24.07± 1.74 mm). In males (333 eyes of 333 patients), mean keratometry ranged between 38.5– 46.95 D (43.54± 1.35 D; p< 0.001), corneal astigmatism ranged between 0.1– 3.97 D (1.15± 0.79; p=0.75), and axial length ranged between 20.41– 31.21 mm (24.57± 1.78 mm; p< 0.001). Both genders presented a shorter axial length in advanced age. Elderly males presented a higher percentage of against-the-rule astigmatism.Conclusion: Females may have steeper corneas and shorter eyes. A trend toward axial length reduction with age was observed in both genders. This finding is probably due to the difference in growth between generations, as the new ones have an higher size than the old ones.Keywords: axial eye length, corneal power, gender, mean keratometry, partial coherence interferometry